Vijana Vijiweni II: a cluster-randomized trial to evaluate the efficacy of a microfinance and peer health leadership intervention for HIV and intimate partner violence prevention among social networks of young men in Dar es Salaam. (December 2015) - Kajula, Lusajo; Balvanz, Peter; Kilonzo, Mrema; Mwikoko, Gema; Yamanis, Thespina; Mulawa, Marta; Kajuna, Deus; Hill, Lauren; Conserve, Donaldson; Reyes, Heathe; Leatherman, Sheila; Singh, Basant; et al.
Abstract Background Intimate partner violence (IPV) and sexually transmitted infections (STIs), including HIV, remain important public health problems with devastating health effects for men and women in sub-Saharan Africa. There have been calls to engage men in prevention efforts, however, we lack effective approaches to reach and engage them. Social network approaches have demonstrated effective and sustained outcomes on changing risk behaviors in the U.S. Our team has identified and engaged naturally occurring social networks comprised mostly of young men in Dar es Salaam in an intervention designed to jointly reduce STI incidence and the perpetration of IPV. These stable networks are locally referred to as "camps." In a pilot study we demonstrated the feasibility and acceptability of a combined microfinance and peer health leadership intervention within these camp-based peer networks. Methods design We are implementing a cluster-randomized trial to evaluate the efficacy of an intervention combining microfinance with health leadership training in 60 camps in Dar es Salaam, Tanzania. Half of the camps have been randomized to the intervention arm, and half to a control arm. The camps in the intervention arm will receive a combined microfinance and health leadership intervention for a period of two years. The camps in the control arm will receive a delayed intervention. We have enrolled 1, 258 men across the 60 study camps. Behavioral surveys will be conducted at baseline, 12-months post intervention launch and 30-month post intervention launch and biological samples will be drawn to test for Neisseria gonorrhea (NG), Chlamydia trachomatis (CT), and Trichomonas vaginalis (TV) at baseline and 30-months. The primary endpoints for assessing intervention impact are IPV perpetration and STI incidence. Discussion This is the first cluster-randomized trial targeting social networks of men in sub-Saharan Africa that jointly addresses HIV and IPV perpetration and has both biological and behavioral endpoints. Effective approaches to engage men in HIV and IPV prevention are needed in low resource, high prevalence settings like Tanzania. If we determine that this approach is effective, we will examine how to adapt and scale up this approach to other urban, sub-Saharan African settings. Trial registration Clinical Trials.gov:NCT01865383 . Registration date: May 24, 2013.